The Moderating Role of Leverage on Corporate Bonds Yield - Sihombing, Pardomuan; Bonowati, Amanda Yosephine; Zakchona, Elia (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 1 (2024): Vol. 17, No. 1, Februari 2024 (pp.1-154), 2024)
This study aims to identify the effect of bond credit rating, firm size, profitability, and liquidity on the yield to maturity (YTM) of listed Indonesian corporate bonds, with leverage ratio as a moderating variable. A panel data multi-linear regression with the fixed effect estimator was used to investigate the YTM of 25 listed corporate bonds from 2019 to 2021. The sample data comprise complete financial reports published in the Indonesia Stock Exchange (IDX) market and operations in the non-financial sector to increase the accuracy of information obtained. The results show that profitability proxied to return-on-asset (ROA) and firm size positively affect the YTM, while the liquidity ratio proxied to the current ratio (CR) had a negative influence. As a moderating variable, leverage proxied to the debt-to-equity ratio (DER) positively moderates the effect of CR, DER negatively moderates the effect of ROA and DER cannot moderate the bond’s credit rating to influence the YTM. However, the bond’s credit rating does not affect the YTM. The analysis of corporate bonds is a relatively uncommon study in Indonesia, and significant implicating for policymakers, underscoring the importance of meticulous management of CR and DER, which can decrease the YTM.